Lung function testing in children: oscillometry. Expert position statement of the Polish Society of Pediatric Pulmonology (STAN PNEUMO: OSCILLOMETRY) - Wasilewska, Eliza; Peradzyńska, Joanna; Walicka-Serzysko, Katarzyna; Krenke, Katarzyna; Doniec, Zbigniew; Mazurek, Henryk; Wojsyk-Banaszak, Irena (Family Medicine & Primary Care Review, 2025)
Respiratory oscillometry is a non-invasive technique for evaluating lung function, particularly advantageous in pediatric populations, as it requires minimal patient cooperation. With the increasing availability of oscillometry in Poland, there is a growing demand for concise guidelines to support its routine clinical application. This article outlines the position of the Polish Society of Pediatric Pulmonology regarding test methodology, indications, and principles of the interpretation of the results. Given the fundamental differences between oscillometry and spirometry, the guidelines emphasize understanding the specific respiratory system components assessed by oscillometry, facilitating the identification of potential dysfunction. Oscillometry holds promise in the diagnosis of obstructive lower airway diseases, such as asthma, bronchopulmonary dysplasia, bronchiolitis obliterans, and the reason for bronchial hyperresponsiveness. Furthermore, it serves as a valuable tool for monitoring disease progression and evaluating treatment efficacy in pediatric patients starting from 3 years of age and across all age groups.